Translation of human Δ133p53 mRNA and its targeting by antisense oligonucleotides complementary to the 5'-terminal region of this mRNA. - Paulina Żydowicz-Machtel (Public Library of Science (PLoS), 2021)
The p53 protein is expressed as at least twelve protein isoforms. Within intron 4 of the human TP53 gene, a P2 transcription initiation site is located and this transcript encodes two p53 isoforms: Δ133p53 and Δ160p53. Here, the secondary structure of the 5'-terminal region of P2-initiated mRNA was characterized by means of the SHAPE and Pb2+-induced cleavage methods and for the first time, a secondary structure model of this region was proposed. Surprisingly, only Δ133p53 isoform was synthetized in vitro from the P2-initiated p53 mRNA while translation from both initiation codons occurred after the transfection of vector-encoded model mRNA to HCT116 cells. Interestingly, translation performed in the presence of the cap analogue suggested that the cap-independent process contributes to the translation of P2-initiated p53 mRNA. Subsequently, several antisense oligonucleotides targeting the 5'-terminal region of P2-initiated p53 mRNA were designed. The selected oligomers were applied in in vitro translation assays as well as in cell lines and their impact on the Δ133p53 synthesis and on cell viability was investigated. The results show that these oligomers are attractive tools in the modulation of the translation of P2-initiated p53 mRNA through attacking the 5' terminus of the transcript. Since cell proliferation is also reduced by antisense oligomers that lower the level of Δ133p53, this demonstrates an involvement of this isoform in tumorigenesis.